THE ROLE OF ARTIFICIAL INTELLIGENCE IN PREDICTING THE OUTCOMES OF TEACHERS’ PROFESSIONAL ACTIVITY (Innovative professional education, 2025)
The role of artificial intelligence in predicting the outcomes of educators’ professional activities has been investigated. It has been established that artificial intelligence enables precise analysis of large datasets, thereby enhancing the efficiency of teaching and the assessment of learning outcomes. A correlation between teaching methodologies and the academic achievements of learners has been identified, contributing to the personalization of education. The application of artificial intelligence as a tool for the professional development of teachers has been proposed. Prospects for improving educational practices in Ukraine through the use of adaptive learning technologies have been explored.
Keywords: artificial intelligence, big data, professional activity, prediction, personalization, educators, learners